The extent of bush encroachment and its effects on the ecosystem services of a mixed bushveld of Makapanstad rangelands, North-West Province, South Africa - Madakadze, Ignacio Casper (University of Pretoria, 2020)
Thesis (PhD (Pasture Science))--University of Pretoria, 2020.